2010
DOI: 10.1007/s00401-010-0777-8
|View full text |Cite
|
Sign up to set email alerts
|

Absence of IDH mutation identifies a novel radiologic and molecular subtype of WHO grade II gliomas with dismal prognosis

Abstract: The phenotypic heterogeneity of low-grade gliomas (LGGs) is still inconsistently explained by known molecular abnormalities in patients treated according to the present standards of care. IDH1 codon 132 and IDH2 codon 172 sequencing was performed in a series of 47 LGGs and correlated with clinical presentation, MR imaging characteristics, genomic profile and outcome. A total of 38 IDH1 mutations at codon 132 and 2 IDH2 mutations at codon 172 were found, including 35 R132H (87.5%), 2 R132C (5.0%), 1 R132S (2.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
195
5
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(227 citation statements)
references
References 51 publications
25
195
5
2
Order By: Relevance
“…15 Chromosomal arms 1p and 19q copy numbers were determined by fluorescence in situ hybridization with locus-specific probes for 1p36 and 19q13, as described elsewhere. 16 No individual investigation of 1p or 19q was considered. …”
Section: Histopathology and Molecular Genetics Studiesmentioning
confidence: 99%
“…15 Chromosomal arms 1p and 19q copy numbers were determined by fluorescence in situ hybridization with locus-specific probes for 1p36 and 19q13, as described elsewhere. 16 No individual investigation of 1p or 19q was considered. …”
Section: Histopathology and Molecular Genetics Studiesmentioning
confidence: 99%
“…8 Apart from its use in difficult diagnostic situations, [8][9][10] mutation of this enzyme also stratifies diffuse gliomas prognostically. 11,12 Recently, recurrent mutations in the promoter region of telomerase reverse transcriptase (TERT), the gene encoding catalytic subunit of telomerase, were detected in B70% of malignant melanomas. 13,14 Mutations caused a cytosine-tothymine transition at the positions of chr5, 1 295 228 (C228T) and 1 295 250 (C250T), and generated an identical 11 base-pair nucleotide sequence (5 0 -CCC CTTCCGGG-3 0 ) containing a consensus binding site (5 0 -TTCC-3 0 ) for E-twenty-six transcription factors.…”
mentioning
confidence: 99%
“…The difference in the frequency of IDH1 mutation may be attributed to sample size, variable sensitivity of the detection assays, or the racial differences can also be taken into consideration. In contrast to IDH1 mutations, IDH2 mutations in gliomas appear to be less frequent with reported incidence ranging between 0.9-4.2% Metellus et al, 2010;Qi et al, 2011;Musaka et al, 2012). Infact, in the current study none of the cases revealed any mutations in IDH2, which is in agreement with previous report (Krell et al, 2011), thereby further suggesting that IDH2 mutations are rare in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast IDH2 mutations are rare, but more common in oligodendroglial tumors, as compared to astrocy¬tomas (Raynaud et al, 2010 protective mechanism in glioma patients which could be the reason for better outcome in patients with mutant IDH than those with the wild-type IDH genes (Zhu et al, 2011). Most of the available studies on IDH1 and 2 mutations are reported from western countries (Bleeker et al, 2009;Metellus et al, 2010;Van den Bent et al, 2010;Cykowski et al, 2012), few reports from Asia (Mukasa et al, 2012;Song Tao et al, 2012), while there is only one report of IDH1 mutations in Indian glioma patients (Jha et al, 2011). In the current study we evaluated IDH1 and IDH2 mutations in glioma patients of different histological types and grades with the aim of assessing their frequency, distribution pattern and their correlation with clinicopathological findings.…”
Section: Introductionmentioning
confidence: 99%